The PA-X host shutoff site 100 V exerts a contrary effect on viral fitness of the highly pathogenic H7N9 influenza A virus in mice and chickens - Xia Chen; Ming Kong; Chunxi Ma; Manyu Zhang; Zenglei Hu; Min Gu; Xiaoquan Wang; Ruyi Gao; Shunlin Hu; Yu Chen; Xiaowen Liu; Daxin Peng; et al. (Virulence)
Several viruses, including influenza A virus (IAV), encode viral factors to hijack cellular RNA biogenesis processes to direct the degradation of host mRNAs, termed “host shutoff.” Host shutoff enables viruses to simultaneously reduce antiviral responses and provides preferential access for viral mRNAs to cellular translation machinery. IAV PA-X is one of these factors that selectively shuts off the global host genes. However, the specific role of PA-X host shutoff activity in viral fitness of IAV remains poorly understood. Herein, we successfully mapped PA-X 100 V as a novel site important for host shutoff of the H7N9 and H5N1 viruses. By analysing the polymorphism of this residue in various subtype viruses, we found that PA-X 100 was highly variable in H7N9 viruses. Structural analysis revealed that 100 V was generally close to the PA-X endonuclease active site, which may account for its host shutoff activity. By generating the corresponding mutant viruses derived from the parental H7N9 virus and the PA-X-deficient H7N9 virus, we determined that PA-X 100 V significantly enhanced viral fitness in mice while diminishing viral virulence in chickens. Mechanistically, PA-X 100 V significantly increased viral polymerase activity and viral replication in mammalian cells. Furthermore, PA-X 100 V highly blunted the global host response in 293T cells, particularly restraining genes involved in energy metabolism and inflammatory response. Collectively, our data provided information about the intricate role of the PA-X host shutoff site in regulating the viral fitness of the H7N9 influenza virus, which furthers our understanding of the complicated pathogenesis of the influenza A virus.